Emotional health as an indicator of youthful well-being - N.S., Svishnikova; A.A, Kasymzhanova; G.O., Abdullaeva; D.T., Ikhsanova; Sandugash, Rapikova (Opción, 2020)
Health is a dynamic concept and is viewed through the prism of human activity. It should be borne in mind that many people are more susceptible to negative environmental influences, which can lead to stress and ill health. In contrast to biological and lifestyle factors, psychosocial factors influence health and behavior through social and cultural aspects. The indicator of age specifics of the subjective state of health is considered as a balance of positive and negative assessments of the state of health of people of different ages, and may depend on the subjective assessment of their mood and well-being.